Multigenic prognosis assessment model for nasopharyngeal carcinoma via a modified meta-analysis approach - Sim, Chor Chien; Edmund, Ui Hang Sim; Lee, Choon Weng; Kumaran, Narayanan (De Gruyter, 2023)
Objectives Currently, clinically relevant multigene-based prognostic assessment models for nasopharyngeal carcinoma (NPC) are limited. This paper reports a novel NPC prognosis assessment model based on multiple established NPC-associated biomarkers.